An axiomatic approach of the discrete Sugeno integral as a tool to aggregate interacting criteria in a qualitative framework. - Marichal, J.-L (IEEE Transactions on fuzzy systems)
We present a model allowing us to aggregate decision criteria when the available information is of a qualitative nature. The use of the Sugeno integral as an aggregation function is justified by an axiomatic approach. It is also shown that the mutual preferential independence of criteria reduces the Sugeno integral to a dictatorial aggregation